Level of Physical Activity and Sedentary Behavior towards Physical Well-Being of Secondary Teachers (International Journal of Scientific Research and Management (IJSRM), 2024)
In contemporary society, characterized by technological advancements and sedentary lifestyles, the significance of physical activity for overall well-being cannot be overstated. Despite global initiatives to promote physical activity and mitigate sedentary behavior, educators, particularly secondary teachers, face unique challenges due to their demanding profession and prolonged periods of sedentary work. The World Health Organization underscores the importance of regular physical activity for maintaining health and well-being, yet many teachers struggle to meet recommended activity levels. The study used a descriptive-correlational research design participated by 60 secondary teachers from Buenavista National High School who are currently teaching during the 2023–2024 school year. Based on the tallied responses, teachers varied widely in age, ranging from 25 to 64 years old, with fewer respondents in their late 50s and 60s. The most common age group was 25 to 34 years old, making up 48.33% of the total sample, and most of them were single. There are more female teachers than male teachers, with females comprising a larger proportion (58.33%) of the total compared to males (41.67%). As revealed, teachers have a moderate level of physical activity and have sedentary behavior. So, even if a person engages in enough physical activity to meet the guidelines, they may still be considered sedentary if they spend a significant portion of their day sitting or lying down at work, at home, for study, travel, or in their leisure time. In teachers’ perceptions to physical well-being, they believed that they didn’t have a normal weight, waist, enough sleep, and good posture. They believe that low physical activity and sedentary behavior have a negative impact on their physical well-being, while at the same time, physical activity and avoiding sedentary behavior are essential for physical well-being. Further, it is depicted that there is no significant correlation between the profile of the respondents and physical well-being and no significant correlation between physical activity and sedentary behavior to physical well-being as well.